Perkembangan Takaful di Malaysia: Satu Kajian Undang-undang Kewangan Islam di Malaysia - Mahmud, Mohd. Sadad; Abd Kader, Radiah (Kanun: Jurnal Undang-undang Malaysia, 2012)
This article inquires into the changes to Islamic finance related laws implemented to support the takaful industry in Malaysia. In addition, this paper will also look at the application of Islamic finance in complying with Islamic law or civil law and its adherence to legal procedures in civil courts as well as the guidelines issued by Bank Negara Malaysia . One of the innovations is the establishment of special courts for the muamalat at the Kuala Lumpur High Court which have clearly opened a space for the development of Islamic muamalat law, and in particular the takaful. Such positive and continued support is much needed to generate a more drastic change and flexibility in the development of the legal infrastructure of Islamic finance in Malaysia, consistent with the intent and goals of the goverment to promote Malaysia as an International Islamic Financial Centre. Keywords: takaful, Malaysia financial law, takaful Law and Islamic financial law.